PENGARUH LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR SISWA KELAS X SMA WIJAYA KUSUMA JAKARTA - Aini Marhamah Aljurah; Nurmawati Nurmawati (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Learning discipline means following guidelines, obeying rules, and upholding relevant ideals are components of discipline. The degree of success and achievement in life is also influenced by discipline. Pre-research observations in class X at SMA Wijaya Kusuma Jakarta during the 2023–2024 academic year revealed certain pupils to have poor learning discipline. This study seeks to investigate whether group counseling services have the potential to enhance student learning disciplin. Group pre-test-post-test design, this study employed a pre-experimental research methodology. A learning discipline questionnaire was employed as part of the data collection process. Using the purposive sample technique, ten students with low learning discipline made up the research subjects. Next, the Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov analysis were performed on the data. The pre-test average was 73.9 and the post-test average was 93.2. The findings of the pre-test and post-test averages show a gain or average difference of 19.3, which indicates that group guidance services are useful for increasing the learning discipline of class X students of SMA Wijaya Kusuma Jakarta in the 2023/2024 school year.